Growth and Development Performance of Hermetia illucens L. (Diptera: Stratiomyidae) Larvae on Fermented Palm Kernel Meal (PKM) Substrate - Damanik, Naomi Florenata; Putra, Ramadhani Eka; Kinasih, Ida; Permana, Agus Dana (Bogor Agricultural University, Indonesia, 2024)
Larvae of Hermetia illucens (Black Soldier Fly/BSF) are considered agents of bioconversion of organic waste, including by-products of agroindustrial waste. Palm kernel meal (PKM), a palm oil mill waste contains high lignocellulose, making it difficult for BSF larvae to digest in which pre treatment process is required. This study aims to analyze the growth and development performance of BSF larvae in fermented PKM waste using EM4 and molasses as the pretreatment process. Five (5) days old BSF larvae were reared in PKM waste, which was fermented with EM4 and molasses for 2, 3, and 4 days (F2, F3, and F4) and with water for four days (FA) while chicken feed (PA) applied as control. During this study, growth rate, average weight, developmental period, survival rate, and larval development period. Feed efficiency and feed reduction analyzed by efficiency of conversion of digested food (ECD), feed conversion ratio (FCR), waste reduction index (WRI) and substrate consumption rate (SCR). The growth and development performance of F2 group was the best among other treatment groups which is similar to larvae fed on chicken feed as a control. All treatments showed high larval survival rates (99.72-100.00%). On the other hand, the best best reduction efficiency recorded in F3. Based on these result it can be concluded that pretreatment of PKM by EM4 and molasses is applicable to be improve the quality of PKM as feeding material for BSF larvae.